IgE-mediated hypersensitivity to chlorhexidine among first- year dental students - Mohamed Khazin, Sobrina; Abdullah, Dalia; Liew, Amy Kia Cheen; Harun, Nor Adilah; Abdullah, Noormalin; Bun, Can Chong (Springer Medizin, 2019)
Purpose To investigate immunoglobulin E (IgE)-medi- ated hypersensitivity to chlorhexidine (CHX), and as- sociation between CHX exposure and serum specific IgE (SIgE) levels, among first-year dental students. Methods Participants completed a questionnaire on medical health, history of allergies/hypersensitivities and CHX exposure. A sample of venous blood (3mL) was drawn and subjected to SIgE test to CHX; sensiti- sation defined as SIgE level of ≥0.10 kUA/L. Results Fifty-eight (98.3%) participants, consisting of 69% (n=40) female with a mean age of 21, were recruited; three quarters (84%) reported no known health issue, and over half had no history of allergies (57%); less than 20% reported having had exposure to CHX-containing products with the majority from toothpaste (9%) and mouthwash (12%). The CHX SIgE test showed that 8.6% (n = 5) were sensitised. No association between CHX exposure history and the level of SIgE antibody was noted. Conclusions Although most participants reported no known exposure to CHX, 8.6% showed CHX sensitisa- tion suggesting unknown exposure and the potential risk of developing hypersensitivity and adverse reac- tions in the future.